Competition‐driven repositioning - Wang, Richard D.; Shaver, J. Myles (Strategic Management Journal, 2014)
We study competition as an impetus for firms to reposition—to abandon their current positioning strategy and adopt a new one. We predict that as a strong firm moves closer, competition erodes the profitability of situated firms and prompts them to reposition. We expect this effect is pronounced the greater difference in competitive strength. However, we expect that countervailing forces exist such that the viability of alternative positions and the opportunity cost of abandoning a current position mitigate this effect. Evidence from a natural experiment in C hina's satellite television industry supports our hypotheses. This research adds to the existing literature on repositioning, which emphasizes the phenomenon as opportunity‐driven, and to the competitive interaction literature, which typically does not distinguish between noncounterattack strategies . Copyright © 2013 John Wiley & Sons, Ltd.